NURS-12. MAKING SURVIVORS HEALTHIER: A MULTIDISCIPLINARY APPROACH TO HYPOTHALAMIC OBESITY. (4th December 2020) - Hemenway, Molly; Dorris, Kathleen; Rydin, Amy; Inge, Thomas; Kelsey, Megan; Hankinson, Todd; Paul, Suzanne; Haemer, Matthew; Moore, Jaime
Abstract: BACKGROUND: Pediatric survivors of hypothalamic/suprasellar tumors have significant morbidities that greatly impact their quality of life. Management of hypothalamic obesity has traditionally fallen between multiple subspecialties without a timely and comprehensive approach. METHODS: A multidisciplinary group of key players from neuro-oncology, endocrinology, nutrition, neurosurgery, and bariatric surgery were identified. Through this collaboration, a clinical algorithm for early identification of and intervention for hypothalamic obesity was developed. The goal of the quality improvement process is to increase the number of encounters with a registered dietitian (RD) with earlier and more consistent referrals to a specialized, multidisciplinary weight management program [Lifestyle Medicine; (LM)] for counseling and pharmacologic interventions. Indications for referral to LM were BMI >95 th percentile, crossing >2 BMI percentiles on growth curve and/or hyperphagia symptoms. A retrospective review of pediatric patients who have suprasellar/ hypothalamic tumors was also conducted. Data collected included demographics, tumor type, BMI, RD visit, and LM clinic referral/visit. RESULTS: Fifty patients were identified for analysis six months following clinical algorithm institution. Thirty-three (66%) patients had craniopharyngioma, 15 (30%) had low-grade gliomas, and two (4%) had germ cell tumors. Thirty-three (66%) patients were noted to be obese (defined as BMI >95 th percentile) at review. The median BMI of the entire cohort was 93 rd (range, 1 st -137 th ) percentile. Thirty-four (68%) patients had been seen by an RD. Twenty-seven (82%) of the obese patients had been referred to LM. CONCLUSIONS: The development and implementation of the process for hypothalamic obesity prevention and intervention will be discussed.